Cultural Heritage: A Tourism Product of Egypt under Risk - MUSTAFA, Mairna H. (Journal of Environmental Management and Tourism, 2021)
The heritage of Egypt is known for its richness and diversity; besides the numerous archaeological and historical sites (tangible heritage), different regions in the country are distinguished for their poetry, songs, dances, handicrafts and other forms of intangible heritage. This paper aims at giving an overview of Egyptian cultural heritage forms, then shedding the light on different threats that hinder their sustainability as tourism cultural resources. An exploratory approach was used in gathering information from literature. The significance of this research comes from the fact that few published works discussed the problems facing heritage in Egypt, particularly, intangible heritage. Clearly, human actions and climate change, globalization, political instability, improper tourism development and social change are all contributing to the erosion of an integral part of the Egyptian culture and social identity. General recommendations were given on ways to save this valuable heritage from loss; these mainly relate documentation, protecting cultural properties, raising awareness and behaviour modification.